Preoperative Neutrophil-to-Lymphocyte Ratio Plus Platelet-to-Lymphocyte Ratio Predicts the Outcomes after Curative Resection for Hepatocellular Carcinoma. (2nd April 2019) - Kabir, T.; Ye, M.; Mohd Noor, N. A.; Woon, W.; Junnarkar, S. P.; Shelat, V. G.
Abstract : Background . In recent years, inflammation-based scoring systems have been reported to predict survival in Hepatocellular Carcinoma (HCC). The aim of our study was to validate combined preoperative Neutrophil-to-Lymphocyte ratio (NLR)-Platelet-to-Lymphocyte ratio (PLR) in predicting overall survival (OS) and recurrence free survival (RFS) in patients who underwent curative resection for HCC. Methods . We conducted a retrospective study of HCC patients underwent liver resection with curative intent from January 2010 to December 2013. Receiver-operating characteristic (ROC) curve analysis was used to determine the optimal cut-off values for NLR and PLR. Patients with both NLR and PLR elevated were allocated a score of 2; patients showing one or neither of these indices elevated were accorded a score of 1 or 0, respectively. Results . 132 patients with a median age of 66 years (range 18-87) underwent curative resection for HCC. Overall morbidity was 30.3%, 30-day mortality was 2.3%, and 90-day mortality was 6.8%. At a median follow-up of 24 months (range 1-88), 25% patients died, and 40.9% had recurrence. On multivariate analysis, elevated preoperative NLR-PLR was predictive of both OS (HR 2.496; CI 1.156-5.389; p =0.020) and RFS (HR 1.917; CI 1.161-3.166; p =0.011). The 5-year OS was 76% for NLR-PLR=0 group, 21.7% for the NLR-PLR=1 group, and 61.1% for the NLR-PLR=2 group, respectively. The 5-year RFS was 39.3% for the NLR-PLR=0 group, 18.4% for the NLR-PLR=1 group, and 21.1% for the NLR-PLR=2 group, respectively. Conclusion . The preoperative NLR-PLR is predictive of both OS and RFS in patients with HCC undergoing curative liver resection.